EXAMINING THE INFLUENCE OF RISK MANAGEMENT STRATEGIES ON FINANCIAL PERFORMANCE A CASE STUDY OF PRIDE MICROFINANCE – MUKONO BRANCH - Tabu Agnes (Uganda Christian University, 2025)
The study examined the influence of risk management strategies on financial performance; A case study of pride microfinance – Mukono branch. The study was guided by the following objectives; to examine the effect of Risk identification on financial performance of pride microfinance Mukono branch, to establish the effect of Risk assessment on financial performance of pride microfinance Mukono branch and to assess the effect of Risk monitoring on financial performance of pride microfinance Mukono branch. The study adapted the descriptive survey design. Amin (2005) describes the survey design as a method that involves collecting information from members of a target population by considering the current status of that population with respect to the study variables. the Key findings included :Respondents perceived risk management strategies positively, with means above 3.8. Correlation analysis showed significant positive relationships between risk identification (r = 0.446, p < 0.01) and risk monitoring (r = 0.422, p < 0.05) with financial performance. Risk assessment was not significant (r = 0.273, p > 0.05).Regression analysis confirmed the model’s significance (R-squared = 0.292, p = 0.012), with risk identification (β = 0.343, p = 0.035) as the strongest predictor, followed by risk monitoring (β = 0.318, p = 0.080). Risk assessment had no effect. Overall, effective risk identification and monitoring enhance financial performance by reducing losses and improving stability. The study concluded that risk management strategies, particularly identification and monitoring, significantly influence financial performance at Pride Microfinance Mukono Branch. Effective identification reduces potential threats like non-performing loans, while monitoring ensures ongoing mitigation, leading to improved profitability and liquidity.
Undergraduate Research